Treatment of Bronchial Asthma with Folk Remedies - Djabbarova Miyassar Bobokulovna (Indonesian Journal of Innovation Studies, 2022)
This article notes that bronchial asthma (BA) is a global problem. Bronchial asthma, the treatment and prevention of which requires only a serious and comprehensive approach, according to WHO, is diagnosed in 4-10% of the world's population. This respiratory disease is chronic, characterized by periodic attacks. The incidence of asthma is increasing worldwide. It is among the top ten non-communicable chronic diseases that are the leading cause of death among middle-aged and elderly people, reducing life expectancy by 6.6 years for men and 13.5 years for women. The purpose of the study was to study the features of the use of non-traditional methods of treating BA along with treatment traditional.